2017
DOI: 10.1091/mbc.e16-12-0820
|View full text |Cite
|
Sign up to set email alerts
|

Two kinesins drive anterograde neuropeptide transport

Abstract: Current anterograde transport models focus on one type of plus-end–directed kinesin for each type of cargo. This study shows that two anterograde motors, kinesin-1 and kinesin-3, both contribute to the transport of neuropeptide-filled vesicles in axons in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 65 publications
8
39
0
1
Order By: Relevance
“…While this kinesin could be kinesin-1 itself, it is also possible that an additional kinesin is involved in transporting outposts. The best candidates for such another kinesin would be kinesin-2 or kinesin-3, which co-transport some cargo with kinesin-1 (Guardia et al, 2016;Gumy et al, 2017;Hendricks et al, 2010;Kulkarni et al, 2017;Lim et al, 2017;Ruane et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While this kinesin could be kinesin-1 itself, it is also possible that an additional kinesin is involved in transporting outposts. The best candidates for such another kinesin would be kinesin-2 or kinesin-3, which co-transport some cargo with kinesin-1 (Guardia et al, 2016;Gumy et al, 2017;Hendricks et al, 2010;Kulkarni et al, 2017;Lim et al, 2017;Ruane et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The large number of kinesin genes raises a fundamental question: Why are so many motors required to fulfill what appears to be the same basic function of moving vesicles towards the plus‐end of microtubules? Some of the kinesin diversity may provide redundancy, but that alone is unlikely to explain the size of the kinesin family. Instead, the diversity could allow different kinesins to confer different transport parameters, targeting vesicles to specific destinations.…”
Section: Introductionmentioning
confidence: 99%
“…With the original BirA ligase this technique has a documented labeling radius of ~10 nm (Kim et al, 2014) and is advantageous over classical coaffinity purification by allowing for detection of transient or weak molecular interactions. We found that a neuronally expressed fusion of the enhanced BirA variant TurboID (Branon et al, 2018) to gain-of-function Rab2 Q65L (TurboID-Rab2 Q65L ) biotinylates the main anterograde Drosophila DCV motor (Barkus et al, 2008;Lim et al, 2017), the Kinesin-3 unc-104 ( Fig. 6C).…”
Section: Rab2 Exhibits Activity-dependent Nanometer-range Proximity Tmentioning
confidence: 96%
“…Anterograde transport is mediated by the diverse family of plus-enddirected kinesin motors, while retrograde transport depends on cytoplasmic dynein. However, a high degree of interdependence exists between anterograde and retrograde transport (Barkus et al, 2008;Lim et al, 2017;Martin et al, 1999;Twelvetrees et al, 2016). Motor recruitment and regulation is mediated by adaptor proteins and small GTPases and is organelle-specific, producing different movement patterns for different organelles (Guedes-Dias and Holzbaur, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation